Prognostic value of epidermal growth factor receptor mutations in resected non-small cell lung cancer: a systematic review with meta-analysis. - Zhixuan Zhang; Ting Wang; Jun Zhang; Xiaohong Cai; Changchuan Pan; Yu Long; Jing Chen; Chengya Zhou; Xude Yin (PLoS ONE, 2014)
Background The prognostic value of epidermal growth factor receptor (EGFR) mutations in resected non-small cell lung cancer (NSCLC) remains controversial. We performed a systematic review with meta-analysis to assess its role. Methods Studies were identified via an electronic search on PubMed, Embase and Cochrane Library databases. Pooled hazard ratio (HR) for disease-free survival (DFS) and overall survival (OS) were calculated for meta-analysis. Results There were 16 evaluated studies (n  =  3337) in the meta-analysis. The combined HR evaluating EGFR mutations on disease free survival was 0.96 (95% CI [0.79-1.16] P  =  0.65). The combined HR evaluating EGFR mutations on overall survival was 0.86 (95% CI [0.72-1.04] P  = 0.12). The subgroup analysis based on univariate and multivariate analyses in DFS and OS showed no statistically significant difference. There was also no statistically significant difference in DFS and OS of stage I NSCLC patients. Conclusion The systematic review with meta-analysis showed that EGFR mutations were not a prognostic factor in patients with surgically resected non-small cell lung cancer. Well designed prospective study is needed to confirm the result.